Sudden cardiac death athletes: a systematic review - Ferreira, Marcelo; Santos-Silva, Paulo R.; de Abreu, Luiz C.; Valenti, Vitor E.; Crispim, Vanessa; Imaizumi, Caio; Filho, Celso F.; Murad, Neif; Meneghini, Adriano; Riera, Andrés R.P.; de Carvalho, Tatiana D.; Vanderlei, Luiz C.M. [UNESP]; et al. (Springer Nature, 2010)
Previous events evidence that sudden cardiac death (SCD) in athletes is still a reality and it keeps challenging cardiologists. Considering the importance of SCD in athletes and the requisite for an update of this matter, we endeavored to describe SCD in athletes. The Medline (via PubMed) and SciELO databases were searched using the subject keywords sudden death, athletes and mortality. The incidence of SCD is expected at one case for each 200,000 young athletes per year. Overall it is resulted of complex dealings of factors such as arrhythmogenic substrate, regulator and triggers factors. In great part of deaths caused by heart disease in athletes younger than 35 years old investigations evidence cardiac congenital abnormalities. Athletes above 35 years old possibly die due to impairments of coronary heart disease, frequently caused by atherosclerosis. Myocardial ischemia and myocardial infarction are responsible for the most cases of SCD above this age (80%). Pre-participatory athletes' evaluation helps to recognize situations that may put the athlete's life in risk including cardiovascular diseases. In summary, cardiologic examinations of athletes' pre-competition routine is an important way to minimize the risk of SCD. © 2010 Ferreira et al; licensee BioMed Central Ltd.
Keywords: age; athlete; athletic performance; cardiovascular risk; cause of death; clinical evaluation; congenital heart malformation; coronary artery atherosclerosis; heart arrhythmia; heart death; heart infarction; heart muscle ischemia; human; hypertrophic cardiomyopathy; left coronary artery; pathophysiology; physical performance; review; sport injury; sudden death; systematic review